Identification of regulatory elements involved in expression and induction by sucrose and UV-B light of the Arabidopsis thaliana COX5b-2 gene, encoding an isoform of cytochrome c oxidase subunit 5b - Comelli, Raul Nicolas (2009)
The promoter sequences required for expression of the Arabidopsis thaliana COX5b-2 gene, encoding an isoform of cytochrome c oxidase subunit 5b, were analyzed using plants transformed with deleted and mutagenized forms of the promoter fused to gus. A 1000-bp promoter fragment produces expression in root and shoot meristems, leaf and cotyledon tips, and anthers. Deletion analysis indicated the presence of positive and negative regulatory elements. A regulatory element located between -660 and -620 from the translation start site was identified as a G-box by mutagenic analysis. Mutation of the G-box, that is present within the coding region of the preceding gene in the genome, increases expression of COX5b-2 in cotyledon and leaf lamina and abolishes induction by ultraviolet-B (UV-B) light, which presumably acts through the removal of an inhibitory factor. Identified positive regulatory elements include a site II element (TGGGCC), a related element with the sequence TGGGTC and four initiator elements (YTCANTYY) that completely abolish expression when mutated in combination. Site II elements are also involved in the response to sucrose. The results imply that the COX5b-2 gene has retained expression characteristics presented by most respiratory chain component genes, but its expression mechanisms have diverged from those employed by COX5b-1, the other gene encoding cytochrome c oxidase subunit 5b in Arabidopsis.